Socio-legal basis of criminal liability of legal persons and corporate compliance to prevent crimes: Anthropic approach and behavioral game theory - Rafael Aguilera Gordillo (Oñati Socio-Legal Series, 2024)
Systems theory has garnered significant criticism from internationally recognized experts in the field of organizational analysis. However, a sector of criminal doctrine is adopting a strict approach to this theory to justify socio-legally the application of corporate criminal liability (this is a trend that has been embraced by the Spanish Supreme Court and is spreading throughout Latin America). The systemic idea of organization excludes the individuals who constitute and manage the company, dehumanizing it, separating corporate governance from the role played by individuals and even attributing human attributes to the company. In other words, the members that make up the organization, as well as the influences or constraints they generate in the context of the interaction of individuals within a corporation, are disregarded in the analysis. As an alternative, this text proposes the essential outlines of an "anthropic model" of corporate criminal liability, which is built on theoretically and experimentally validated notions and methodologies: neo-institutionalism, game theory and behavioral compliance. In this anthropic model, the adoption and implementation of an effective and adequate governance system to prevent irregularities (or crimes) does not depend on the system itself, but depends directly on the commitment and implementation of the "human component" of the organization.